2007
DOI: 10.2133/dmpk.22.409
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Metabolic Interaction of Nateglinide with Other Drugs Based on in Vitro Studies

Abstract: Nateglinide is an antidiabetic agent metabolized by CYP2C9 and CYP3A4; hence inhibitors of these CYP isozymes may interact with nateglinide. There are, however, only limited in vitro data on how to predict drug-drug interactions in vivo. We examined the effects of 18 drugs that may be prescribed together with nateglinide (metformin, buformin, aspirin, gemfibrozil, simvastatin, pioglitazone, rosiglitazone, carbamazepine, clarithromycin, gliclazide, clofibrate, fluconazole, bezafibrate, phenylbutazone, nifedipin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…Throughout the present study, a wide range of (S)-(ϩ)-IBU and (R)-(Ϫ)-IBU concentrations was used (1-500 M). Such a range encompasses the clinically relevant free (ϳ1 M) and total (ϳ100 M) plasma concentrations of each enantiomer (Davies, 1998;Andersson et al, 2004;Takanohashi et al, 2007). Integration of the above in vitro data, with known human ADME information, may help rationalize reports describing IBU PK-P450 inhibitor combinations and IBU PK-P450 genotype associations (Kirchheiner et al, 2002;Garcia-Martin et al, 2004;Martinez et al, 2005;Hynninen et al, 2006;Bell et al, 2007;Tornio et al, 2007).…”
Section: Cyp2c8 Plays a Minor Role In (R)-(؊)-ibu (<10%) And (S)-(؉)-mentioning
confidence: 99%
“…Throughout the present study, a wide range of (S)-(ϩ)-IBU and (R)-(Ϫ)-IBU concentrations was used (1-500 M). Such a range encompasses the clinically relevant free (ϳ1 M) and total (ϳ100 M) plasma concentrations of each enantiomer (Davies, 1998;Andersson et al, 2004;Takanohashi et al, 2007). Integration of the above in vitro data, with known human ADME information, may help rationalize reports describing IBU PK-P450 inhibitor combinations and IBU PK-P450 genotype associations (Kirchheiner et al, 2002;Garcia-Martin et al, 2004;Martinez et al, 2005;Hynninen et al, 2006;Bell et al, 2007;Tornio et al, 2007).…”
Section: Cyp2c8 Plays a Minor Role In (R)-(؊)-ibu (<10%) And (S)-(؉)-mentioning
confidence: 99%
“…It is worth noting that Dostalek et al reported that only patients with poor glycemic control exhibit changes in the activities of metabolic enzymes. Moreover, previous studies have demonstrated that the metabolism of tolbutamide by CYP2C9 is not changed in diabetes patients and that metformin is unlikely to exert any influence on carvedilol pharmacokinetics because apparently metformin is not a substrate, inducer, or inhibitor of CYP enzymes …”
Section: Discussionmentioning
confidence: 99%
“…Unlike many non-aspirin NSAIDs, aspirin is not primarily metabolized by CYP2C9 3740. Thus, it is unlikely that this association reflects genotype-specific differences in tolerance to aspirin therapy.…”
Section: Discussionmentioning
confidence: 99%